Studi Kasus Santriwati Halaqoh Khotm Islamic Center Bin Baz dalam Memilih Jurusan Kuliah - Qiyadah Robbaniyah; Roidah Lina; Amelia Falensyana (At Turots: Jurnal Pendidikan Islam, 2022)
The number of students who are still confused in choosing college majors, the selection of college majors should be adjusted to the interests and talents that are already known from experience, previous education. This research was conducted based on a case study experienced by 3 (three) female students of the Halaqah Khotm Islamic Center Bin Baz had difficulty choosing a college major. The purpose of this study is to find out in-depth what are the factors causing the difficulties of female students of Halaqoh Khotm in choosing college majors. This research method is a descriptive qualitative method. The approaching model used is a case study, data collection by observation and interviews. The results of the study were found that the factors causing the difficulties of Halaqoh Khotm female students in choosing college majors were they did not know their personality, did not know their talents, lack of knowledge of various professions, and the existence of unresolved obstacles in female students that hindered female students in their future. the front. In carrying out the case study, the researcher conducted 2 sessions, namely; first, a briefing that involved researchers, a teaching cleric at the Halaqoh Khotm Islamic Center Bin Baz, and 2 clerics who were competent in their fields. Second, assistance in making plans. From the results of the mentoring of female students using a coaching approach and the themes are taken are the making of plans related to ideals, the design of the Sanad taking the program, the design of self-development, the design of household skills, the design of the selection of college majors.